Bilateral hydronephrosis due to obstructive ureteral stone associated with norovirus gastroenteritis. Issue 6 (2nd May 2017) - Ochi, Fumihiro; Furuno, Kenji; Chong, Pin Fee; Tezuka, Junichiro; Mizuno, Yumi; Aoki, Tomonobu; Ishii, Eiichi
Key Clinical Message: Recently, cases of urinary tract calculi causing hydronephrosis and postrenal renal failure associated with viral gastroenteritis were documented, yet few were related to norovirus. During norovirus gastroenteritis, observation of oliguria, aciduria, low FENa value, and elevation of blood or urinary uric acid level may necessitate clinical workout for nephrolithiasis. Abstract : Recently, cases of urinary tract calculi causing hydronephrosis and postrenal renal failure associated with viral gastroenteritis were documented, yet few were related to norovirus. During norovirus gastroenteritis, observation of oliguria, aciduria, low FENa value, and elevation of blood or urinary uric acid level may necessitate clinical workout for nephrolithiasis.